Ways Of Government Regulation Of The Food Market - Shavkat Oltaev (Research Parks Publishers, 2023)
This article analyzes the significant measures of state regulation of the food market to ensure political and socio-economic stability, to use consistent incentive mechanisms for increasing production volume. A scientific conclusion and practical recommendations aimed at the implementation of comprehensive measures by the state in the food market have been developed.